2013
DOI: 10.5430/jnep.v4n3p188
|View full text |Cite
|
Sign up to set email alerts
|

Attitudes toward caring for dying patients: An overview among Italian nursing students and preliminary psychometrics of the FATCOD-B scale

Abstract: Background: Extensive research indicated that nursing students at the end of their curricula feel unprepared to care for the dying. Therefore, studies on nursing students' attitudes to caring for dying patients play a key role in nursing education, and the FATCOD-B scale is the only tool that specifically evaluates them. Methods:A cross-sectional study design was used. During 2013, the FATCOD-B scale was administered to a sample of 82 nursing students. Descriptive statistics, the Student's t-test, Cronbach's a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
44
4
6

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 36 publications
(63 citation statements)
references
References 30 publications
9
44
4
6
Order By: Relevance
“…Focusing on the relationship with the dying patient during care, rather than on death and dying as general concepts, the Frommelt Attitude Toward Care of the Dying Scale Form-B (FATCOD-B) (Frommelt, 1991; appears to be a useful instrument for end-of-life care education because it provides information about the behavior of the health professionals in clinical practice. The original version of the scale, named FATCOD, had been developed for nurses (Frommelt, 1991); subsequently, the FATCOD was slightly modified in FATCOD-B to be administered to students coming from different programs of study (Frommelt, 2003 Leombruni et al, 2014a). All of these studies come from nursing education research and, despite its potential for use in medical education, the FATCOD-B scale has rarely been administered to medical students (Leombruni et al, 2012;2014b).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Focusing on the relationship with the dying patient during care, rather than on death and dying as general concepts, the Frommelt Attitude Toward Care of the Dying Scale Form-B (FATCOD-B) (Frommelt, 1991; appears to be a useful instrument for end-of-life care education because it provides information about the behavior of the health professionals in clinical practice. The original version of the scale, named FATCOD, had been developed for nurses (Frommelt, 1991); subsequently, the FATCOD was slightly modified in FATCOD-B to be administered to students coming from different programs of study (Frommelt, 2003 Leombruni et al, 2014a). All of these studies come from nursing education research and, despite its potential for use in medical education, the FATCOD-B scale has rarely been administered to medical students (Leombruni et al, 2012;2014b).…”
Section: Introductionmentioning
confidence: 99%
“…Not surprisingly, recent examinations of the factor structure of the FATCOD-B have found alternatives to the single dimension conceptualization; two dimensions (Nakai et al, 2006;Henoch et al, 2013a) and even four dimensions (Leombruni et al, 2014a) have been suggested. These studies, which were data driven using variable reduction techniques such as principal component analyses, were explorative and, although compelling solutions were proposed, these have not been confirmed.…”
Section: Introductionmentioning
confidence: 99%
“…19,20 The FATCOD-B consists of 30 randomly ordered items scored on a 5-point Likert-type scale. Half of the statements are positively worded and half are negatively worded.…”
Section: Instrumentsmentioning
confidence: 99%
“…The possible total score ranges from 30 to 150 and a higher score indicates a more positive attitude toward the care of dying patients. 19,20 For the personality assessment of the subjects, the Temperament and Character Inventory (TCI) was used. 21 The TCI is a true-false questionnaire with 240 questions that assess personality by describing aspects of temperament and character.…”
Section: Instrumentsmentioning
confidence: 99%
“…Part II: "Frommelt Attitude Toward the Care of the Dying Scale form B (FATCOD-B)" that is a psychometric instrument, developed by Frommelt (26,27) and is translated in to Arabic by the researcher. The scale is designed to measure nurses' attitudes toward caring for terminally ill persons and their families.…”
Section: Toolmentioning
confidence: 99%